Enhancement of lipase stability and productivity through chemical modification and its application to latex-based polymer emulsions - Jayawardena, MB; Yee, LH; Poljak, A; Cavicchioli, R; Kjelleberg, SJ; Siddiqui, KS (Process Biochemistry, 2017)
The primary focus of this research was to employ amino-group specific chemical modifications for improving the productivity and stability of two commercially produced lipases, Lipase-A from Candida antarctica (CALUM) and Greasex from Humicola lanuginosa (HLLUM), for application in a latex-based paint formulation. The modified lipases showed higher percentage increase (benzoic anhydride-modified, HLLBA, 150%; PEG-modified, HLLPEG,162% at 75 °C) as well as higher absolute productivities 41, 50, 52 and 53 μmole substrate mg−1 lipase for unmodified, CALPEG, HLLPEG and HLLBA, respectively at 37 °C. The half-lives of thermal inactivation for all modified variants were improved from 40 to 166% at 50, 60 and 70 °C relative to unmodified lipases. The higher thermal stability and catalytic efficiency (kcat/Km) with concomitant lower activity (kcat) indicates that enhanced productivity is likely to be due to the modified enzymes being better able to resist thermal denaturation over the time course of the productivity experiments. Importantly, both lipases, CALBA (60%) and HLLBA (55%) retained the highest activity in paint compared with CALUM (36%) and HLLUM (39%) after 20 weeks incubation at 25 °C. The long term stability of the modified lipases illustrates their potential value for commercial paint and other industrial applications.